Za m’eskuze… Za vous emmerde : entre le colonial et le postcolonial, le travail de mémoire dans la prose de Jean-Luc Raharimanana - Zatorska, Izabella (Romanica Silesiana)
<!--EndFr-->The combination of two traditional Malagasy genres, kabary and sovâ, to produce the monologue of a desperate father named “Za” — whose name signifies an intimate, familiar “Me” — engenders the narrative situated between two realities: the world of the living and the world of the dead. This intersection serves to describe the banally apocalyptic reality in which today’s Madagascar is immersed. Surrounded by characters drawn from legends and from his own previous works, Raharimanana — a novelist, poet and playwright who was born in 1967 and has lived for the past twenty years in France — begins a work of memory by confronting the emblematic shadows of Malagasy history. Everything is expressed through the author’s language, which, via lisping, reveals unsuspected meanings and imposes on words the mutilation that Raharimanana’s narrator had to endure. It also elicits images of injuries inflicted on the author’s father in 2002. Following in the path of Frankétienne and Sony Labou Tansi, the initial narrative denounces taboos, such as respect for ancestors. Garbled French becomes a neology appropriate for an analysis of the postcolonial reality as well as for defining the attitude of one who fervently refuses to adopt a monolithic approach towards it. Key words: Madagascar, kabary, sovâ, postcolonial literature, memory.